Digital Marketing Strategies and Brand Awareness of Afrinnovators Group Ltd - Benegusenga, Samuel; Akims, Malgit (International Journal of Strategic Marketing Practice, 2024)
Purpose: In today's digital age, the significance of digital marketing strategies in enhancing brand awareness among businesses was emphasized. This research aimed to assess the influence of digital marketing strategies on brand awareness in Rwanda, focusing on Afrinnovators Group Ltd. The study had three objectives: to evaluate the impact of different digital marketing channels, the effect of digital marketing expenditure, and the role of social networking platforms on brand awareness. Methodology: The theoretical framework reviewed Bandura's Social Learning Theory, Howard's Consumer Behavior Theory, and Rogers' Diffusion of Innovation Theory. A mixed-method approach was employed, involving quantitative and qualitative research designs. The target population included 102 individuals, with a sample size of 81 respondents determined using Slovin's formula. Data analysis involved descriptive and inferential statistics for quantitative data and thematic analysis for qualitative data. Findings: Regression analysis highlighted digital marketing expenditure as the most significant predictor of brand awareness, with an unstandardized coefficient of 0.096 (p = 0.022). Other predictors included social media marketing with a coefficient of 0.085 (p = 0.035) and search engine marketing with a coefficient of 0.078 (p = 0.041). The study concluded that strategic digital marketing efforts profoundly impacted brand awareness for Afrinnovators Group Ltd. Unique Contribution to Theory, Practice and Policy: Recommendations included prioritizing social media marketing, enhancing email and search engine campaigns, and investing in online ads and videos. Future research was suggested to explore long-term effects, emerging technologies, and comparative studies to optimize digital marketing strategies. This study contributed to academic knowledge, offered practical implications for businesses, and aligned with Sustainable Development Goals by promoting economic growth.